Perceived Information Overload and Intention to Discontinue Use of Short-Form Video: The Mediating Roles of Cognitive and Psychological Factors - Donghwa Chung; Yuanxin Chen; Yanfang Meng (Behavioral Sciences, 2023)
The current study investigated the effects of Chinese young adult users’ perceived information overload (i.e., the daily perception of exposure to excessive information) on their intention to stop using short-form video applications. Specifically, this study accomplished this by measuring the direct and indirect effects of social media fatigue, maladaptive coping, and life dissatisfaction in relation to users’ intention to discontinue their use of short-form video applications. The data were collected using a web-based survey and validated questionnaire, with a sample of 340 young adult (18–26 years old) respondents. The results indicated that perceived information overload had a direct effect on the intention to discontinue the use of short-form video applications. Moreover, short-form video fatigue, maladaptive coping, and life dissatisfaction all played mediating roles in the relationship between perceived information overload and the intention to discontinue the use of short-form video applications among young adults in China.